Physical activity at work may not be health enhancing. A systematic review with meta-analysis on the association between occupational physical activity and cardiovascular disease mortality covering 23 studies with 655 892 participants - Cillekens, Bart; Huysmans, Maaike A.; Holtermann, Andreas; van Mechelen, Willem; Straker, Leon; Krause, Niklas; van der Beek, Allard J.; Coenen, Pieter (Scandinavian Journal of Work, Environment & Health, 2022)
' ' OBJECTIVES ': 'Emerging evidence suggests contrasting health effects for leisure-time and occupational physical activity. In this systematic review, we synthesized and described the epidemiological evidence regarding the association between occupational physical activity and cardiovascular disease (CVD) mortality. ' ' METHODS ': 'A literature search was performed in PubMed, Embase, CINAHL, PsycINFO and Evidence-Based Medicine Reviews, from database inception to 17 April 2020. Articles were included if they described original observational prospective research, assessing the association between occupational physical activity and CVD mortality among adult workers. Reviews were included if they controlled for age and gender and at least one other relevant variable. We performed meta-analyses on the associations between occupational physical activity and CVD mortality. ' ' RESULTS ': 'We screened 3345 unique articles, and 31 articles (from 23 studies) were described in this review. In the meta-analysis, occupational physical activity showed no significant association with overall CVD mortality for both males [hazard ratio (HR) 1.00, 95% confidence interval (CI) 0.87–1.15] and females (HR 0.95, 95% CI 0.82–1.09). Additional analysis showed that higher levels of occupational physical activity were non-significantly associated with a 15% increase in studies reporting on the outcome ischemic heart disease mortality (HR 1.15, 95% CI 0.88–1.49). ' ' CONCLUSIONS ': 'While the beneficial association between leisure-time physical activity and CVD mortality has been widely documented, occupational physical activity was not found to have a beneficial association with CVD mortality. This observation may have implications for our appreciation of the association between physical activity and health for workers in physically demanding jobs, as occupational physical activity may not be health enhancing.
Keywords: cardiovascular disease; cardiovascular mortality; CVD; meta-analysis; occupational physical activity; physical activity; systematic review